ANALISIS PERLINDUNGAN HUKUM KONSUMEN TABUNGAN EMAS PADA E-COMMERCE TOKOPEDIA - Suprapdi Suprapdi; Abdul Mujib (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2023)
AbstractThis article aims to analyze the legal protection of consumers digital gold savings in e-commerce transactions on Tokopedia. Digital gold savings is a product of gold buying and selling services with deposit facilities at very affordable prices. This service is one form of the business operation of pawnshop companies as a deposit service provider institution that has been mandated in SEOJK No. 52/SEOJK.05/2017. Along with the development and advancement of technology, PT. Pegadaian collaborates with e-commerce, one of which is Tokopedia, to encourage the public to invest in gold only through their smartphones. This authorship uses normative juridical methods. The results showed that legally, the regulation regarding business actors (PT. Pegadaian and e-commerce) is required to guarantee legal protection of consumer rights, including ensuring legal protection for consumers in the event of an increase or decrease in gold prices that fluctuate every day. While digital ownership of gold in Islamic law is included in imperfect ownership because it is only in the form of gold balances (intangible).Keywords: legal protection; online gold savings; e-commerce.